2013
DOI: 10.1016/j.jdiacomp.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The association between skin collagen glucosepane and past progression of microvascular and neuropathic complications in type 1 diabetes

Abstract: PURPOSE We determined the association between novel and acid-labile skin collagen-linked advanced glycation endproducts (AGEs) and the progression of microvascular and neuropathic complications from baseline to near study closeout in the Diabetes Control and Complications Trial (DCCT). METHODS From a skin biopsy obtained near the close of the DCCT, proteolytic collagen digests were analyzed by liquid chromatography/mass spectrometry (LC/MS/MS) for glucosepane (GSPNE), glyoxal and methylglyoxal hydroimidazolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 41 publications
1
58
1
Order By: Relevance
“…These modifications are produced by reaction of aldehydes and ketones with amino groups of lysine and arginine. Long-lived extracellular proteins such as skin collagen (Vishwanath et al, 1986; Genuth et al, 2015; Monnier et al, 2013) and eye lens protein (Perry et al, 1987) and retina have been shown to be targets of these carbohydrate-mediated reactions but nonenzymatic glycation occurs also on short-lived proteins (Bidasee etal., 2003). The pentosidine modification identified in DAF of diabetic patients is known to induce crosslinking involving the nearby R residues.…”
Section: Discussionmentioning
confidence: 99%
“…These modifications are produced by reaction of aldehydes and ketones with amino groups of lysine and arginine. Long-lived extracellular proteins such as skin collagen (Vishwanath et al, 1986; Genuth et al, 2015; Monnier et al, 2013) and eye lens protein (Perry et al, 1987) and retina have been shown to be targets of these carbohydrate-mediated reactions but nonenzymatic glycation occurs also on short-lived proteins (Bidasee etal., 2003). The pentosidine modification identified in DAF of diabetic patients is known to induce crosslinking involving the nearby R residues.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasively assessed skin AGEs were also associated with retinopathy in the DCCT/EDIC cohort [173]. Skin collagen AGEs measured biochemically on skin biopsies were independent predictors of diabetic retinopathy (and other microvascular complications) in the DCCT/EDIC cohort [174][175]. Recently, a panel of 10 AGEs measured chemically in skin biopsy collagen taken near DCCT close-out has been shown to be predictive of the subsequent retinopathy status [50].…”
Section: Factors Related To Advanced Glycation Endproducts (Ages)mentioning
confidence: 99%
“…The aging of organism is accompanied by structural and functional modifications of macromolecules [70]. The changes that occur in the tissues of the organism under the development of diabetes mellitus are investigated both in laboratory animals using experimental models [9][10][11]17, 39, 40, 42, 45-47, [71][72][73][74][75][76][77] and directly in patients in the course of clinical examination [12,35,[78][79][80][81][82][83][84][85][86][87].…”
Section: Classification Of Diabetes Mellitusmentioning
confidence: 99%
“…All of them show a sufficiently effective glycation of proteins during 10-11 days of incubation, a change in the mechanical properties of tissues due to the formation of collagen cross-links. In work [82], an increase in the glucosapane content in the skin with age and with the development of hyperglycemia in patients with type 1 diabetes mellitus was recorded. After eight months of glycation of the rabbit Achilles tendon in ribose solution [139] the increased maximum load, deformation stress, Young modulus of elasticity, and viscosity, indicating the fact that the glycation increases the stiffness of the tendon matrix, were observed.…”
Section: Glycation and Non-enzymatic Glycation Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation